Dairy Farm Women's Information Seeking Patterns Involvement in Farm Decision Making - Jean O'Brien (Journal of Applied Communications, 1986)
Farm women have expressed strong needs for more and better educational and informational programs. Recent research suggests that farm women are playing an active role in information seeking and farm decision making.